2006
DOI: 10.4314/just.v26i1.32965
|View full text |Cite
|
Sign up to set email alerts
|

Design innovations towards enhancing the quality of living in multi-storey compound housing for low-income households in Kumasi, Ghana

Abstract: A large number of low-income households in Kumasi, in the Ashanti Region, live in compound houses. The earlier compound houses built in mud are mostly single-storey but this has gradually metamorphosed, over the years, into multi-storey compound houses within the urban areas. This has been attributed mainly to the high land values and efforts by landlords to maximize the use of land, thereby absorbing the large number of urban poor who lack accommodation. The incidence of a large number of rooms with this kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The buildings with window-to-wall ratios below the recommended range are largely among the single-family private housing typology. Interestingly such spaces have higher occupancy densities and the function of the spaces double as both sleeping and living areas, as observed by [37].…”
Section: Evaluation Of Bio-climatic Design Features Of Residential Building Typologiesmentioning
confidence: 64%
“…The buildings with window-to-wall ratios below the recommended range are largely among the single-family private housing typology. Interestingly such spaces have higher occupancy densities and the function of the spaces double as both sleeping and living areas, as observed by [37].…”
Section: Evaluation Of Bio-climatic Design Features Of Residential Building Typologiesmentioning
confidence: 64%
“…Currently, the Ashanti region, whose capital is Kumasi, has the largest numerical share of compound houses in the Ghana; more than 52% of all houses in the region are compound houses (Ghana Statistical Service, 2012). More to the point, majority of past studies on compound houses (such as Willis and Tipple, 1991;Afram, 2007;Afram and Owusu, 2006;Arslan, 2011;Korboe, 1992) were all conducted in Kumasi. Therefore, no other location in Ghana could have been more appropriate for a study of this kind.…”
Section: 1 Study Methodologymentioning
confidence: 99%
“…Over the years, the sharing of common space and facility has been at the centre of many problems in compound houses in urban Ghana. Afram and Owusu (2006) found a number of tenants' complaints about the sharing of facility or space in a compound house. Firstly, they found that, most tenants had problem with the principle of equal sharing of electricity bills, especially where some households use more electrical gadgets than others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation